“DE-CENTERING INSTITUTIONS AS OBJECTS OF STUDY” - Valverde, Mariana (REI - REVISTA ESTUDOS INSTITUCIONAIS, 2020)
My travels through the vast field of socio-legal studies have not included time in the ‘law and development’ subfield, and so my comments here will not speak to Mariana Mota Prado and Michael Trebilcock’s contribution to that literature in their book, Institutional Bypasses. Instead I will speak from the perspective of sociolegal research on governance.